2017
DOI: 10.4337/ejeep.2017.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Review of exchange-rate theories in four leading economics textbooks

Abstract: In this paper, the parts of four leading economics textbooks that deal with exchange-rate theories are reviewed. The books are by Krugman/Obstfeld/Melitz, Blanchard/Johnson, Mankiw/Taylor and Samuelson/Nordhaus. The theoretical background for this exercise is the fact that exchange-rate theory is one of the weakest parts in 'mainstream economics', meaning the neoclassical and the New Keynesian stream of thought. It is now widely accepted that exchange-rate forecasts are no better than those arising from a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Demand and supply of money in any given country depend on such factors like real income levels, general price levels, interest rates and decisions of monetary policy authorities, which ultimately means that foreign exchange rate is derived from the interaction between these factors for any two given countries. Priewe (2017) argues that advocates of monetary theory interpret exchange rate as the relationship of money stocks (money stock reflects the general price levels) of one country and the other. Thus, the differentials and interactions between money stocks of any two countries determine the rate of exchange for the currencies of the said countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Demand and supply of money in any given country depend on such factors like real income levels, general price levels, interest rates and decisions of monetary policy authorities, which ultimately means that foreign exchange rate is derived from the interaction between these factors for any two given countries. Priewe (2017) argues that advocates of monetary theory interpret exchange rate as the relationship of money stocks (money stock reflects the general price levels) of one country and the other. Thus, the differentials and interactions between money stocks of any two countries determine the rate of exchange for the currencies of the said countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The exchange rate policy in Ghana since 1986 means that the rate is not controlled and therefore susceptible to fluctuations from one period to the other. Priewe (2017) emphasizes the importance of assessing distortions in the economy in determining exchange rate movements by criticizing strict adherence and lack of empirical support by some economics authors on the subject of exchange rate theories as discussed. This means that the subject of exchange rate determination should not be considered in isolation on theoretical basis but should be looked at holistically, in terms of deviations from fundamentals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This approach implicates that the short run is only a temporary disequilibrium that leads after some time to a general macro equilibrium. The short-term disequilibrium is healed eventually by market forces (Priewe, 2017).…”
Section: The Condition Of Equilibrium Exchange Ratementioning
confidence: 99%
“…It is widely accepted, however, that exchange rate forecasts are no more accurate than those arising from a random walk in both short and medium term, and empirical validation is weak for long horizons. In 2017, a review of exchange rate theories in four leading economic textbooks revealed little empirical support for the theories examined, see Priewe (2017). There has been a general consensus about poor performance in comparison with benchmark random walk models for more than three decades, following seminal papers by Rogoff (1983a, 1983b).…”
Section: George E P Boxmentioning
confidence: 99%